2021
DOI: 10.3390/jcm10235662
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Mortality of Emergency Patients Transported by Emergency Medical Service Personnel during the Novel Corona Virus Pandemic in Osaka Prefecture, Japan: A Population-Based Study

Abstract: Although the COVID-19 pandemic affects the emergency medical service (EMS) system, little is known about the impact of the COVID-19 pandemic on the prognosis of emergency patients. This study aimed to reveal the impact of the COVID-19 pandemic on the EMS system and patient outcomes. We included patients transported by ambulance who were registered in a population-based registry of patients transported by ambulance. The endpoints of this study were the incident number of patients transported by ambulance each m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…In contrast, reports in Japan showed that the overall number of suicide victims in Japan increased during the COVID‐19 pandemic, 8 , 9 , 10 and the time required to deliver prehospital care to victims of traffic accidents, which included mild‐to‐severe patients, did not change in the early stage of the COVID‐19 pandemic. 3 However, no reports examined the epidemiology, management, or mortality of major trauma patients during the COVID‐19 pandemic in Japan, and clarifying these points will be informative for suitable provision of emergency medical care when a new infectious disease pandemic occurs in the future.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, reports in Japan showed that the overall number of suicide victims in Japan increased during the COVID‐19 pandemic, 8 , 9 , 10 and the time required to deliver prehospital care to victims of traffic accidents, which included mild‐to‐severe patients, did not change in the early stage of the COVID‐19 pandemic. 3 However, no reports examined the epidemiology, management, or mortality of major trauma patients during the COVID‐19 pandemic in Japan, and clarifying these points will be informative for suitable provision of emergency medical care when a new infectious disease pandemic occurs in the future.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies also found a drop in admissions for acute cardiovascular and nervous system diseases during the initial COVID peak [ 4 , 5 , 6 , 7 , 8 , 9 , 24 ]. The decrease was observed especially during the complete and partial lockdown periods, whereas these indicators increased during the de-escalation period.…”
Section: Discussionmentioning
confidence: 82%
“…During the first wave of the pandemic, various studies reported a decrease in emergency department (ED) visits, hospital admissions related to non-COVID conditions [ 3 , 4 , 5 , 6 , 7 ], and consultations in primary care [ 8 ]. Non-COVID respiratory diseases and cardiovascular emergencies seem to be the most affected conditions described to date [ 4 , 5 , 9 , 10 , 11 ], but there have also been reports of reductions in cerebrovascular and traumatology admissions [ 5 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The impact of COVID-19 on the care activity of Hospital Emergency Departments (ED) has been studied in large hospitals in Paris (France), Tehran (Iran) and Osaka (Japan) [24][25][26]. However, no studies have been found where an intrahospital comparison has been performed, that is, showing the results of the care activity performed both in the ED and in other departments of the same hospital, comparing the year prior to the pandemic (2019) versus the year of the pandemic (2020).…”
Section: Impact Of the Covid-19 Pandemic In Spain Through 2020mentioning
confidence: 99%